Dari Masa Kolonial Hingga Revolusi Fisik: Jejak Eksistensi Pangkalan Udara Militer Panasan Surakarta (1940-1949) - Dadan Adi Kurniawan (Jambura History and Culture Journal, 2019)
The air military is an important part of supporting the strength and sovereignty of a country. In gathering strength, the air military generally has a center (headquarters) that is in a "base". This center or headquarters was then called the Military Air Base. This role is also assumed by the Panasan Air Military Base in Surakarta. One of the air military forces on the island of central Java has been around since the Dutch colonial era. This base is a silent witness to a trip of three eras, namely the Netherlands, Japan and independence. This research aims to trace the standing, background of its establishment, until its development until the early period of Indonesian independence, especially the period of physical revolution (1946-1949).